Critical discourse analysis of Philippine SONA 2006 of President Gloria Macapagal Arroyo - Gocheco, Paulina M. (Animo Repository, 2007)
This paper analyzes the State of the Nation Address (SONA) of President Macapagal Arroyo delivered on July 24, 2006. The framework used is critical discourse analysis (CDA) to unravel any hidden agenda in the speech. The study aims to investigate the relationship between language features such as language switching, structure of text, visual images used in the presentation, other styles in discourse such as the frequent use of names in the text vis-a-vis the Philippine social and political environment today. Specifically, the study aims to examine 'acknowledgement', a highly significant feature in the structure of the 2006 SONA, language switching, technology and the rationale behind them. The study reveals that amidst the social and antagonistic political environment that the country is in today, President Macapagal Arroyo attempted to win the approval of the Filipino people through the language features used in the SONA. Also, the SONA is an annual political event that serves as an opportunity for the President to use language as strategy to serve the various political functions needed for governance.